Hubungan Aktivitas Fisik Terhadap IMT Mahasiswa FKM Universitas Mulawarman Selama Pandemi Covid-19 - Mifthahul Mifthahul Jannah (UPPM Poltekkes Kemenkes Ternate, 2022)
Background: Since restrictions of public activity were implemented to prevent Covid-19 spreading, it also limited physical activity. Low physical activity is a risk factor for various comorbidities such as obesity, diabetes, hypertension which made more susceptible to severe Covid-19 disease. Purpose: To determine the association between physical activity and body mass index in Mulawarman University, Faculty of Public Health students during the Covid-19 pandemic. The study used an observational method with cross-sectional design with 197 sample. The instrument used Global Physical Activity Questionnaire (GPAQ) from WHO, collected by online questionnaire and analyzed using a chi-square test. Results: The mean of physical activity was 1498.23 MET (Metabolic Equivalent) and dominated by moderate activity (brisk walking, mopping floors, cleaning the house, moving furniture, gardening, planting trees, washing motorbikes or cars) the nutritional status dominated by normal nutritional status (60.4%) but there were still (4,6%) underweight and (10,2%) obesity. Based on the results of the Chi-square test, it showed an association between physical activity and body mass index p-value = 0.048. Conclusion: It could be concluded that there was an association between physical activity and body mass index in Mulawarman University Faculty of Public Health students during the Covid-19 pandemic